PEMODELAN 3D PULAU BATU MANDI MENGGUNAKAN DIGITAL ELEVATION MODEL (DEM) TURUNAN DIGITAL SURFACE MODEL (DSM) SHUTTLE RADAR TOPHOGRAPHY MISSION (SRTM) 90 DENGAN INTERPOLASI COKRIGING - Atriyon Julzarika (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2009)
Pulau Batu Mandi is one of the 92 small outlying islands of Indonesia. This island has a common boundary with Malaysia and it is needed a 3D model to see the topography condition of that island. In this research, that modelling uses the data input of Digital Surface Model (DSM) SRTM90 and is added by one basepoint and one reference point and also some bathymetry points. All data are merged to produce a new DSM using the CoKriging interpolation. Then the DSM2DEM operation is performed to transform the derived DSM of CoKriging interpolation to be a DEM 7 m. The spline interpolation is then performed toward the DEM 7 m to provide a smoother display. The DEM 7 m has a spatial resolution of 7 m with the vertical accuracy litlle than 5m after performing a geostatistical test globally to the reference data. This condition uses 3σ tolerance to fulfill the mapping criteria for the possibility of 1m sea level rise. This DEM 7 m can be used for engineering and non-engineering aplications Keywords: Pulau Batu Mandi, DSM, DEM, CoKriging Interpolation